2021
DOI: 10.1017/s000711452100180x
|View full text |Cite
|
Sign up to set email alerts
|

Iron-biofortified pearl millet consumption increases physical activity in Indian adolescent schoolchildren after a 6-month randomised feeding trial

Abstract: Background: Iron deficiency has negative effects on voluntary physical activity (PA); however, the impact of consuming iron-biofortified staple foods on voluntary PA remains unclear. This study compared the effects of consuming iron-biofortified pearl millet or a conventional pearl millet on measures of voluntary PA in Indian school children (ages 12-16 years) during a six-month randomized, controlled feeding trial. PA data were collected from 130 children using Actigraph GT3X accelerometers for six days at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Total iron absorption from iron-biofortified pearl millet composite meals was double than regular meals (Cercamondi et al, 2013). An earlier bioefficacy study indicated that students from Indian schools had a 65% decrease in iron deficiency due to the daily intake of 232 g of iron-biofortified pearl millet flour (Pompano et al, 2022). These results support the use of biofortified millets as a sustained food strategy for populations facing a greater risk of iron deficiency.…”
Section: Biofortified Foodmentioning
confidence: 71%
“…Total iron absorption from iron-biofortified pearl millet composite meals was double than regular meals (Cercamondi et al, 2013). An earlier bioefficacy study indicated that students from Indian schools had a 65% decrease in iron deficiency due to the daily intake of 232 g of iron-biofortified pearl millet flour (Pompano et al, 2022). These results support the use of biofortified millets as a sustained food strategy for populations facing a greater risk of iron deficiency.…”
Section: Biofortified Foodmentioning
confidence: 71%
“…17 The sixth study was conducted at the Pennsylvania State University with the subjects being female students. 18 The 7th and 8th study were conducted in India 19 and Newcastle University, Australia, 20 while the ninth study was conducted in Maharashtra, India with the subjects being female students aged 12-16 years. 21 The tenth study was conducted in El Minya province, Upper Egypt with the subjects being female teenagers.…”
Section: Resultsmentioning
confidence: 99%